2020
DOI: 10.3390/medicina56020051
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate’s Effect on Tongue Mucosa: An Experimental Electron Microscopy Study

Abstract: Background and objectives: Bisphosphonates (BPs) are selective inhibitors of osteoclasts, used for the treatment of bone disorders. The objective of this study is to investigate the possible effects of BPs on the tongue’s mucosa. Materials and Methods: Specimens of the tongue of 20 female 12-month old Wistar rats were taken. Ten were used as control group, while in the remaining alendronate (Fosamax, Merck) was administered per os from 13 weeks. Observation of the harvested samples was made by Transmission Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Group III (Fosamax-treated group): Rats of this group were administered 0.05mg/kg of Fosamax dissolved in 0.5 ml of normal saline solution orally by a gastric tube once weekly for 13 weeks. The Fosamax dose was calculated according to the usual human dose [18] .…”
Section: The Animals Were Divided Into Four Equal Groups (Ten Animalsmentioning
confidence: 99%
“…Group III (Fosamax-treated group): Rats of this group were administered 0.05mg/kg of Fosamax dissolved in 0.5 ml of normal saline solution orally by a gastric tube once weekly for 13 weeks. The Fosamax dose was calculated according to the usual human dose [18] .…”
Section: The Animals Were Divided Into Four Equal Groups (Ten Animalsmentioning
confidence: 99%
“…Bisphosphonates have been shown to affect the adhesion of various types of cells including epithelial cells 8 , endothelial cells 33 and cancer cells 34 . It has also been reported that bisphosphonates are associated with esophagitis and oral ulceration 8,26,35,36 . Experiments using in vitro models of the oral mucosa have shown that pamidronate and zoledronate reduce the viability, inhibit the proliferation and enhance the apoptosis of oral keratinocytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…21 In a recent in vitro study has been suggested that the decrease in the number of hemidesmosomes noticed after administration of alendronic acid could indicate the formation of ulcerous lesions in murine buccal mucosa. 23 Consequently, bisphosphonates may interfere in regenerative, apoptotic and ultrastructural cellular processes, leading to the development of mucosal adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate toxicity to gastrointestinal cells is well documented 14,16,17 . Recent in vitro studies provide evidence that high doses of oral bisphosphonates may also have a negative impact on the oral mucosa 21‐24 . Doneti et al (2014) suggested that alendronic acid may have a negative effect on keratinised oral human mucosa of osteoporotic patients without clinical signs of MRONJ, 22 whilst recent experimental studies in animals have demonstrated that alendronic acid can induce an inflammatory process in the buccal and tongue mucosa 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation